2018
DOI: 10.1002/lpor.201800155
|View full text |Cite
|
Sign up to set email alerts
|

Parity‐Time‐Symmetric Optical Lattice with Alternating Gain and Loss Atomic Configurations

Abstract: Since the periodic parity‐time (PT)‐symmetric potential can possess unique properties compared to a single PT cell (with only two coupled components), various schemes have been proposed to realize PT symmetry in optical lattices. Here, a PT‐symmetric optical lattice is experimentally constructed with simultaneous gain and loss in an atomic medium. The gain and loss arrays are created in the four‐level N‐type configurations excited by spatially alternating strong and weak pump fields, respectively, which do not… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(28 citation statements)
references
References 60 publications
0
28
0
Order By: Relevance
“…We have examined the far-field Fraunhofer diffraction off a thin 2D atomic lattice subject to transversely periodic cross modulations, including pure PT -symmetry ones as well as hybrid ones as a combination of Hermitian, PT -symmetry, and non-Hermitian modulations along two orthogonal axes. These spatial modulations, now realizable through standard laboratory routines [66], can be all-optically controlled to generate nontrivial far-field patterns that span from double diagonal symmetric diffraction in two diagonal quadrants to single axial symmetric diffraction in two adjacent quadrants and single diagonal symmetric diffraction in a single quadrant. These patterns appear to be fairy robust against standard sources of noises (fluctuations), e.g., in the atomic density or in the intensity of trapping or pumping lasers [67].…”
Section: Discussionmentioning
confidence: 99%
“…We have examined the far-field Fraunhofer diffraction off a thin 2D atomic lattice subject to transversely periodic cross modulations, including pure PT -symmetry ones as well as hybrid ones as a combination of Hermitian, PT -symmetry, and non-Hermitian modulations along two orthogonal axes. These spatial modulations, now realizable through standard laboratory routines [66], can be all-optically controlled to generate nontrivial far-field patterns that span from double diagonal symmetric diffraction in two diagonal quadrants to single axial symmetric diffraction in two adjacent quadrants and single diagonal symmetric diffraction in a single quadrant. These patterns appear to be fairy robust against standard sources of noises (fluctuations), e.g., in the atomic density or in the intensity of trapping or pumping lasers [67].…”
Section: Discussionmentioning
confidence: 99%
“…Nonlinear optics is a new field in optical theories which is becoming more and more mature 2125 . And now it has been done well in experiments 2628 . The optical rectification effect is a process of generating a low-frequency electrode field (THz) by the interaction of a pulsed laser and a nonlinear medium, and belongs to a special nonlinear optical effect 29,30 .…”
Section: Introductionmentioning
confidence: 91%
“…On the other hand, nonlinear processes can lead to asymmetric wave propagation without the need of an external magnetic field. Recent experimental advances have demonstrated that nonlinear optical lattices with alternating gain and loss atomic configurations are ideal realizations of non-Hermitian parity-time symmetric systems that can be explored to better understand the peculiar physical properties of these non-Hermitian systems in atomic settings [15,16].…”
Section: Introductionmentioning
confidence: 99%